2017
DOI: 10.1007/s00421-016-3533-5
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity initiated by employer induces improvements in a novel set of biomarkers of inflammation: an 8-week follow-up study

Abstract: PurposeWe investigated the level of pro- and anti-inflammatory biomarkers before and after 8 weeks of unsupervised physical activity (PA) initiated by employer.MethodsDuring autumn 2014, background data, blood samples and self-reported exercise level were collected from 76 men and 41 women in a Norwegian road maintenance company. Monocyte chemoattractant protein-1 (MCP-1), tumor necrosis factor-alpha (TNF-α), interleukin-6 (IL-6), leptin, adiponectin, p-selectin and CD40 ligand (CD40L) were analyzed. was meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 41 publications
1
16
0
1
Order By: Relevance
“…The effects of voluntary wheel running on the neuroimmune reactions of mice were found to be modulated by MCP-1 (Spielman et al 2017). Our finding that there was already a reduction in MCP-1 after 2 weeks of Pilates exercise complements the findings of others who reported that, in long term physical activity regimes, total levels of biomarkers of inflammation improved (Lunde et al 2017). Similarly, endurance training (ET) reduced inflammatory markers (TNF-α, IL-6), macrophage recruitment (MCP-1 and F4/80) and increased the IL-10/TNF-α ratio in plasma (Rocha-Rodrigues et al 2017).…”
Section: Discussionsupporting
confidence: 87%
“…The effects of voluntary wheel running on the neuroimmune reactions of mice were found to be modulated by MCP-1 (Spielman et al 2017). Our finding that there was already a reduction in MCP-1 after 2 weeks of Pilates exercise complements the findings of others who reported that, in long term physical activity regimes, total levels of biomarkers of inflammation improved (Lunde et al 2017). Similarly, endurance training (ET) reduced inflammatory markers (TNF-α, IL-6), macrophage recruitment (MCP-1 and F4/80) and increased the IL-10/TNF-α ratio in plasma (Rocha-Rodrigues et al 2017).…”
Section: Discussionsupporting
confidence: 87%
“…Physical exercise is also effective at the molecular level, as it exerts its effects on the AMPK/sirtuins/peroxisome proliferator-activated receptor network, and upregulates oxidative metabolism, while downregulating biosynthesis and inflammation [13]. Moreover, physical exercise ameliorates quality of life, stimulates the production of antiinflammatory cytokines, decreases the levels of leptin, and increases adiponectin levels and adiponectin receptor activity [94,95].…”
Section: Physical Exercisementioning
confidence: 99%
“…The current study describes the 15-month follow-up from a cohort of office and road workers that took place in an eight-week leisure time PA-program initiated by the employer [ 20 , 21 ]. The enterprise management organized the 8-week unsupervised intervention in which the idea was to increase PA.…”
Section: Introductionmentioning
confidence: 99%
“…Beneficial effects on lipid status and an increase in maximal oxygen uptake (VO 2max ) were found at the end of the intervention [ 20 ]. The markers of inflammation P-selectin and CD40 L were decreased in the total group, along with a decrease in MCP-1 among men [ 21 ]. The study included both women and men.…”
Section: Introductionmentioning
confidence: 99%